ALGORITHM FOR ORDERING CASCADES OF NONRECURSIVE DIGITAL FILTERS BASED ON A GENETIC ALGORITHM - Петросян, Руслан; Петросян, Арсен; Локтікова, Тамара; Кузьменко, Олександр (SWorldJournal, 2023)
The paper proposes an algorithm for ordering FIR filter cascades based on a genetic algorithm to minimize the error arising from the quantization of multiplication results. Choosing the optimal order of arrangement of cascades is a difficult problem, as i